Effects of Marketization and Corporate Social Responsibility on Brand Value - Wu, Xinwu (Business Administration and Management Journal Review, 2023)
This paper introduces the system theory and other theoretical perspectives to study the relationship between marketization degree, corporate social responsibility and brand value. This paper uses empirical research method, introduces institutional theory and other theories to make research hypothesis, selects data of A-share listed companies in the List of "China’s 500 Most Valuable Brands" of the World Brand Laboratory from 2009 to 2018, and conducts empirical analysis on the hypothesis using STATA15.0 software. The results show that the degree of marketization has a positive promotion effect on brand value through corporate social responsibility, and internal control has a negative adjustment effect on the promotion effect of corporate social responsibility on brand value. This paper forms the research path of "marketization degree – Corporate social responsibility – brand value", which enriches the research in the field of system theory and so on.